1990
DOI: 10.1016/0014-5793(90)80642-v
|View full text |Cite
|
Sign up to set email alerts
|

Members of the α‐amylase inhibitors family from wheat endosperm are major allergens associated with baker's asthma

Abstract: We have identifi~ the major antigens or IgE binding components from wheat tIour. Thirty-five sera from patients with baker's asthma were used to analyze the reaction with wheat salt-soluble proteins. We found a 15 kDa SDS-PAGE band which reacted with all sera tested. Purified members of the a-amylase inhibitor family, which are the main components of the 15 kDa band, were recognized by specific IgE when tested with a pool of reactive sera. Immunodetection after two-dimensional electrophoretic fractionation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 27 publications
2
70
1
Order By: Relevance
“…Most of these inhibitors isolated from wheat, barley and rice are recognized by specific IgE when tested with sera from allergic patients (Barber et al, 1989;García-Casado et al, 1995;Gómez et al, 1990;Izumi et al, 1992;Sanchez-Monge et al, 1992;1996a,b). However, their IgE-binding capacities in vi tro are very different .…”
Section: Allergenic Propertíesmentioning
confidence: 99%
“…Most of these inhibitors isolated from wheat, barley and rice are recognized by specific IgE when tested with sera from allergic patients (Barber et al, 1989;García-Casado et al, 1995;Gómez et al, 1990;Izumi et al, 1992;Sanchez-Monge et al, 1992;1996a,b). However, their IgE-binding capacities in vi tro are very different .…”
Section: Allergenic Propertíesmentioning
confidence: 99%
“…More than 10 homologous cDNA clones encoding the 14-16 kDa allergens have been obtained so far [8], indicating that the 14-16 kDa allergens are multigene products. DNA sequencing revealed that these cDNA clones all encoded proteins similar to wheat a-amylase inhibitor, barley trypsin inhibitor and the castor bean storage protein [9], which had been identified as major allergenic proteins associated with baker's asthma [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is mainly caused by allergens present in wheat flour. Some of these allergens, such as fungal ␣-amylase, are derived from contaminants or additives (41), whereas others represent genuine wheat proteins or glycoproteins (18,22,23,42). At present, only few genuine wheat allergens have been identified, and it is not yet clear whether they are specific for baker's asthma or whether they are also recognized by patients suffering from wheat-associated food allergy or grass pollen allergy (26).…”
Section: Discussionmentioning
confidence: 99%
“…They include the members of the ␣ amylase inhibitor family (22), acyl-CoA oxidase, peroxidase (23), fructosebisphosphate aldolase, and recently thioredoxins (18). However, the great majority of the soluble wheat flour allergens have not yet been identified (24).…”
mentioning
confidence: 99%